Public Service Innovation in Indonesia 2013-2023: Combination Analysis of Open Knowledge Map and VOSViewer - ., Widyawati; Sakawati, Herlina; ., Sulmiah (KnE Social Sciences, 2024)
Public service innovation is important to overcome the imbalance between human resources and the high level of demand for services by the community. However, this is still not understood by public sector organizations in general. This study is here to examine the dynamics of implementing innovation in Indonesia in the last 10 years. The study was carried out using the literature review search method which combines the Open Knowledge Map (OKM) and Vos Viewer (VV) applications. The data were processed by following the application procedures used, then analyzed by adopting some of the principles of qualitative methods. OKM is used to map public service innovation clusters, while VV’s role is to look at public service innovation clusters with different analyses and sources. The results of the analysis show that innovation in Indonesia is dependent on leadership, which can be an obstacle to the long-term sustainability of innovation. The level of participation and competitiveness of public service innovations has not been evenly distributed throughout Indonesia. There is still a need for strategies and policy directions for collaboration and involvement of the private sector in public service innovation. The combination of digitalization and administration innovations is an innovation that has been carried out in the last 10 years. Barriers to the implementation of public service innovations are generally a problem that often occurs in other public organizations. Keywords: innovation, public service, public organization